Intrapleural combination therapy with lobaplatin and erythromycin for non‐small cell lung cancer‐mediated malignant pleural effusion. Issue 8 (19th June 2018) - Xu, Lisheng; Wang, Benjie; Gao, Meimei; Zhang, Yan; Qi, Qian; Li, Tao; Li, Caiyu; Wang, Aihua; Li, Yu
Abstract : Background: Malignant pleural effusion is a common complication of non‐small cell lung cancer (NSCLC); however, treatment options remain limited. This study evaluated the safety and efficacy of sequential intrapleural therapy with lobaplatin and erythromycin for NSCLC‐mediated malignant pleural effusion. Methods: Fifty‐six patients with NSCLC complicated with malignant pleural effusion were recruited for a prospective single‐arm study from December 2014 to 2016; one patient dropped out. In addition to conventional systemic chemotherapy, lobaplatin and erythromycin were intrapleurally injected into subjects. Short and long‐term responses were analyzed. The concentration of ultrafilterable platinum in the pleural effusion and plasma were detected at different time points. Incidences of severe adverse reactions were observed. Results: In the 55 evaluable patients, the effective rate of pleural effusion was 81.8% after six weeks of treatment. Six and twelve months after treatment, the effective rates were 60% and 21.8%, respectively, and the one‐year survival rate was 83.6%. The concentrations of lobaplatin in pleural effusion and plasma two hours after injecting 50 mg lobaplatin into the thoracic cavity were 13.763 ± 1.523 μg/mL and 1.120 ± 0.164 μg/mL, and 17 hours later were 1.961 ± 0.351 μg/mL and 0.578 ± 0.095 μg/mL, respectively. The rate of severe adverse reactions of the first cycle of systemic chemotherapy combined with lobaplatin and erythromycin did not significantly differ from the rate in the second cycle. Conclusion: Intrapleural combination therapy with lobaplatin and erythromycin is a safe and efficient treatment for patients with NSCLC‐mediated malignant pleural effusion.